Easy method for discriminating the origins of manila clam Ruditapes philippinarum with a dual-labelled PNA-probe-based melting curve analysis - Kim, Eun-Mi; Song, Min Sik; Hur, Deok Hwe; An, Cheul Min; Kang, Jung-Ha; Park, Jung Youn (Biochip journal, 2015)
Probe-based fluorescence melting curve analysis is a powerful tool used to detect mutations, based on the melting temperature from the thermal denaturation of the probe-target hybrid. PNA (Peptide nucleic acid) probes have several advantages: easy to design and modify and do not give false negative results. In this study, we developed and applied a MeltingArray method using PNA-probe-based fluorescence melting curve analysis to quickly determine the origins of manila clams. Five PNA probes were designed to discriminate between imported (from Dalian, China) and domestic (Korea) manila clams and positioned at KRph27135, KRph29263 and KRph37987. The KRph 37987-159C PNA probe had the highest discrimination ability. The KRph37987-159C probe had perfect match binding with the domestic manila clams at 80.8-100%, and mismatch binding with the imported manila clams excluding heterozygous samples at 66.7-76.8%. Moreover, domestic manila clams were discriminated by the PNA probes KRph29263-143G and KRph29263-205C at a ratio of 96.8% and 100%, and the imported manila clams were discriminated 100% and 98.5%, respectively. Here, we report that domestic and imported manila clams can be distinguished by the MeltingArray system and that it is a more rapid, simple and accurate method than that of sanger sequencing. The dual-labeled PNA probes offer the advantage of improved flexibility in probe design, which could be used in future applications for genotyping a wide range of subjects.